Preferences on how to measure and discuss health related quality of life within integrated care for children with obesity - Minke M. A. Eilander; Marieke M. A. van Mil; Leandra W. Koetsier; Jacob C. Seidell; Jutka Halberstadt (SpringerOpen, 2021)
Abstract Background Childhood obesity can affect physical as well as psychosocial wellbeing. Therefore, childhood obesity care aims to improve all dimensions of health related quality of life (HRQoL). HRQoL can be measured with the generic questionnaire PedsQL4.0 and the weight-specific IWQOL-Kids. In the Netherlands, HRQoL assessment is conducted by the coordinating professional (CP). The aim of this qualitative study was to examine how and when to implement the measurement and discussion of HRQoL using the PedsQL4.0 and IWQOL-Kids within the integrated care for children with obesity in the Netherlands. Semi-structured interviews were conducted with fourteen CPs, in which the following was discussed: a) familiarity and attributions with regard to the assessment of HRQoL; b) wishes and needs with regard to the usage of the questionnaires; c) its practical incorporation. Results Interviews revealed that most CPs gained insight into the HRQoL by talking with families. One CP used the PedsQL4.0, the remaining CPs were unfamiliar with the two questionnaires. Even though some barriers, for instance a lack of time, might hinder the implementation of the PedsQL4.0 and IWQOL-Kids, all participants think the usage of either one or both questionnaires would have additional value to the support and care for children with obesity. There was no consensus about the questionnaire of preference. Conclusions When the right preconditions are met, HRQoL questionnaires have the potential to support CPs in improving the care for children with obesity, tailored to each individual child.